PEMANFAATAN TEPUNG KACANG MERAH (Phaseolus vulgaris L) DALAM PEMBUATAN SNACK BAR - Sidiq; Utomo, Deny (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2025)
Red beans (Phaseolus vulgaris L) are a local food ingredient rich in nutrients such as protein, fiber, vitamins, and antioxidants. This study aimed to determine the effect of red bean flour utilization on the chemical and organoleptic properties of snack bars, and to identify the most acceptable formulation based on nutrition and sensory quality. The research used a Completely Randomized Design (CRD) with one factor, consisting of three treatments of red bean flour proportions (100%, 75%, 50%) and three replications. Observed parameters included moisture, ash, protein, fat, carbohydrates, and hedonic tests for color, aroma, taste, and texture. The results indicated that different proportions of red bean flour significantly affected all chemical and organoleptic parameters. The best formulation was found in the 50% red bean flour treatment, with moisture content of 20.56%, ash 1.25%, protein 4.06%, fat 9.59%, and carbohydrates 64.54%, along with the highest hedonic scores in taste and texture (score 4, like). It can be concluded that red bean flour has strong potential as an alternative ingredient in developing functional food products in the form of snack bars